Learning to resist: exploring habitus (trans)formation of critical teacher-activists before 1994 - Visagie, Ashley (School of Education, 2025)
This study aims to understand the enabling conditions for the emergence of teacher activism before South Africa's democratic transition in the 1990s. It does so by examining the life experiences of four teacher activists that became politically active in their childhood and youth, and who entered the field of teaching during apartheid. The study contributes to a growing body of literature about the lives of teachers during apartheid, while offering theoretical insight into the emergence of teacher activism under apartheid. Four teachers were selected for the study, all of whom were classified as ‘coloured' males under apartheid. All four identify as socialists and all four participated in the anti apartheid struggle and held various positions of leadership. While they began their teaching careers at different times and the length of their teaching careers differ for various reasons, including banning, imprisonment and dismissal, they embodied in their own ways what it means to be critical teachers. Methodologically, this study critically analyses life-stories, drawing from in-depth narratives produced through semi-structured interviews. This approach allowed for an engagement with rich data on personal perspectives and recollections, as well as broader social influences in the lives of the teachers in this study. The primary concern of the study is to understand the enabling conditions for the emergence of teacher activism during apartheid, which it explores through an analysis of the accounts of the four designated teachers. Treating memory as a repository of precious knowledge, the goal is to offer a variety of insights that serve as a heuristic framework to think about the arguable absence of teacher social movements in South Africa in the contemporary period. Leveraging conceptual resources drawn from Bourdieu, the insights which this study has produced demonstrate that the emergence of activism may be better understood by considering how times of crisis produce conditions under which taken-for-granted assumptions can be contested. Crisis produces discordance within the field between hegemonic social visions and the reality of the crisis, which renders plausible resistance discourses. Such times of crisis can be experienced at the level of the individual in moments that are referred to in this study as critical incidents, and they are also experienced collectively at the broader societal level, as Bourdieu has suggested. In the above regard, the primary contribution of the study lies in its engagement with the role of imagination as a form of intellectual labour at moments of crisis, where machinations of power are made more explicit but where imagining a more hopeful future is also catalysed. Both of these processes are necessary in converting crises into catalytic events capable of mobilising people, and that then spurs different forms of activism. A further contribution emerges from the study's engagement with different collective processes of organisation such as trade unions, history societies, or sports clubs that offer spaces that promote the acquisition of two forms of capital, namely critical capital and organising capital, and that create places where counter-hegemonic imaginations can be cultivated. The study shows how changing situations in the lives of different teacher activists simultaneously constrain possibilities for change and produce contradictions (or contradictory conditions) that provide the required room for activist intervention. These lessons, it is argued, offer important insights into how teacher activism is constituted and how, perhaps, it can arguably be revived in the contemporary period.